0041 Circadian Misalignment Increases The Desire For Food Intake In Chronic Shift Workers. (27th April 2018) - Qian, J; Caputo, R; Morris, C J; Wang, W; Scheer, F A
Abstract: Introduction: Shift workers face increased risk of obesity and frequently experience misalignment between their circadian system and behavioral/environmental cycles. While emerging evidence suggested that such circadian misalignment can acutely disrupt energy homeostasis in healthy adults accustomed to a day schedule, little is known about its acute impact on chronic shift workers. Here we examined the effects of circadian misalignment on ratings of hunger and appetite, the hunger hormone ghrelin, and energy expenditure in chronic shift workers. Methods: Seven healthy chronic shift workers (mean ± SD, age 37 ± 7 y, BMI 24.4 ± 3.2 kg/m 2, 3 men) each underwent two highly controlled 3-day laboratory visits in a randomized cross-over design: a circadian alignment protocol and circadian misalignment protocol (12-h inverted behavioral and environmental cycles). Participants consumed an isocaloric diet per 24 h. Identical test meals were given 1h and 13 h following scheduled wake time. Energy expenditure was derived from indirect calorimetry measurements for these test meals sessions. Hourly active ghrelin concentrations and self-rating of hunger and appetite were assessed. Daily locomotor activity was recorded by actiwatch. Results: Circadian misalignment led to a 17% increase in 24-h active ghrelin levels in the chronic shift workers (P<0.05). Consistently, they also had 38% higher desire to eat at both test meals in the circadian misalignment protocols (P<0.05). Circadian misalignment did not significantly change fasting and postprandial energy expenditure or respiratory exchange ratio (all P>0.32). Unexpectedly, their 24-h locomotor activity levels were 27% higher (P<0.05) in the circadian misalignment protocol despite concurring increases in sleepiness (P<0.05). Conclusion: Our results suggest that circadian misalignment increases the drive for food intake in chronic shift workers, partly through increasing the hunger hormone ghrelin. Further studies are needed to test whether the paradoxical rise in activity levels during night work can counteract the potential energy gain in the long term. Support (If Any): Study was supported in part by (NHLBI) Grant R01 HL094806 to FAJLS and CTSA UL1RR025758 to Harvard University and Brigham and Women's Hospital.